Reactive oxygen species-mediated cancer therapy with silica-based nanoparticles - Ong, Wee Kong (Nanyang Technological University, 2020)
Reactive oxygen species (ROS) is important for the well-being of cells since they served as messengers. However, too much ROS will kill them because of their high reactivity with DNA and surrounding organelles.